INDEKS MASSA TUBUH BERHUBUNGAN DENGAN KECEPATAN DAN KELINCAHAN ATLET - Dharmajayanti, Ida Ayu Laksmi; Negara, Anak Agung Gede Angga Puspa; Artini, I Gusti Ayu (Kinetic and Physiotherapy Comprehensive, 2023)
Background: Athletes are prepared to adapt their body composition to the their sports. Biomotor components such as agility and speed are certainly one of important components to support the performance of an athlete. It is necessary to know more about the suitability of body composition needed for each sport that can improve performance in athletes. This study aimed to determine the relationship between BMI, speed, and agility among athletes. Methods: This study used a literature review design to discuss the relationship between BMI, speed, and agility among athletes based on secondary data from published literature on Google Scholar and PubMed. The inclusion criteria used include: journals describing correlation between the body mass index, speed, and agility among athletes, journals published between 2015-2023. The exclusion criteria used include: excluding other articles if there are duplicates, excluding abstracts, theses, and dissertations. Results: Based on the results of a review of five studies that discussed body mass index on speed and agility in athletes, it was found that four journals stated that there were significant relationships between BMI, agility, and speed, but there was one journal which found an insignificant relationship between BMI and agility for male athletes but it was significant for female athletes. Conclusion: Agility and speed in athletes have a relationship with each BMI category. Athletes who were in the underweight BMI category would have better agility and speed compared to athletes who were in the overweight.